2009
DOI: 10.1097/nmd.0b013e3181bb0d6b
|View full text |Cite
|
Sign up to set email alerts
|

Violent Behavior in Acute Psychiatric Inpatient Facilities

Abstract: Violence committed by acute psychiatric inpatients represents an important and challenging problem in clinical practice. Sociodemographic, clinical, and treatment information were collected for 1324 patients (677 men and 647 women) admitted to Italian public and private acute psychiatric inpatient facilities during an index period in 2004, and the sample divided into 3 groups: nonhostile patients (no episodes of violent behavior during hospitalization), hostile patients (verbal aggression or violent acts again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 70 publications
5
34
0
1
Order By: Relevance
“…This finding is consistent with findings from studies on the associations with violence at individual patient level. For example, male sex and substance use disorders have been found to be reliably associated with aggression both in individual studies [2830] and in meta-analysis [15]. Both male sex and alcohol abuse are strongly associated with violence among mentally ill outpatients, and by non-mentally disordered people in the general community.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with findings from studies on the associations with violence at individual patient level. For example, male sex and substance use disorders have been found to be reliably associated with aggression both in individual studies [2830] and in meta-analysis [15]. Both male sex and alcohol abuse are strongly associated with violence among mentally ill outpatients, and by non-mentally disordered people in the general community.…”
Section: Discussionmentioning
confidence: 99%
“…Females often have a better course and outcome (Addington and Addington, 2008;Grossman et al, 2006;Häfner and an der Heiden, 1999;Perkins et al, 2005), and they are less likely to suffer from substance abuse, social drift and law infringement (Biancosino et al, 2009;Cantor-Graae et al, 2001;Romm et al, 2010;Thorup et al, 2007;Walker et al, 1985). Better outcome in women was not always reported in non-Western countries (Rangaswamy and Greeshma, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…8,9 Although its main function is to compare changes in psychopathology, studies have revealed an association between factors of this scale and aggression in hospital environments. [10][11][12][13][14] This study assessed the severity of psychopathology and investigated possible associations with aggressive behaviors in the first 24 hours after psychiatric hospitalization to define whether aggressiveness was associated with the severity of psychosis and psychomotor agitation.…”
mentioning
confidence: 99%